Students Experiences in Navigating Listening Challenges with World Englishes: A Phenomenological Study - Kurniasih, Cicih; Alfaridzi, Wahdan Fauzan; Abdurrahman, Teguh; Darsih, Endang (Proceedings Series on Social Sciences & Humanities, 2025)
This study explores the challenges that students of English Education face in comprehending listening texts with accent variation within the framework of World Englishes. Using a qualitative phenomenological research design, the data were obtained through semi-structured interviews with ten students of the sixth semester of Kuningan University who had studied the World Englishes elective course. The results showed that the major difficulties comprised unfamiliar types of accents (such as Indian, Singaporean, and British accents), speed of speech, interference from background noise, and the use of unfamiliar local words and idioms. To cope with these, the students used a variety of coping strategies such as replay of audio, use of subtitles, increased exposure to varied accents through digital media, and the use of technology such as online dictionaries and artificial intelligence. The experiences of lecturer support differed; while some students felt supported by the diverse materials, others relied on self-study mechanisms. The study concluded that while there were complex difficulties in comprehending World Englishes, the students demonstrated enormous flexibility in self-study. The findings point to the need to develop a more inclusive listening curriculum and pedagogy that explicitly embraces global accent differences to prepare students for communication in real-life contexts.